EMG-Informed Musculoskeletal Modeling to Estimate Realistic Knee Anterior Shear Force During Drop Vertical Jump in Female Athletes - Navacchia, Alessandro; Ueno, Ryo; Ford, Kevin R.; DiCesare, Christopher A.; Myer, Gregory D.; Hewett, Timothy E. (Annals of biomedical engineering, 2019)
The anterior cruciate ligament is the primary structural restraint to tibial anterior shear force. The anterior force occurring at the knee during landing contributes to anterior cruciate ligament injury risk, but it cannot be directly measured experimentally. The objective of this study was to develop electromyography-informed musculoskeletal simulations of the drop vertical jump motor task and assess the contribution of knee muscle forces to tibial anterior shear force. In this cross-sectional study, musculoskeletal simulations were used to estimate the muscle forces of thirteen female athletes performing a drop vertical jump using an electromyography-informed method. Muscle activation and knee loads that resulted from these simulations were compared to the results obtained with the more common approach of minimization of muscle effort (optimization-based method). Quadriceps–hamstrings and quadriceps–gastrocnemius co-contractions were progressively increased and their contribution to anterior shear force was quantified. The electromyography-informed method produced co-contraction indexes more consistent with electromyography data than the optimization-based method. The muscles that presented the largest contribution to peak anterior shear force were the gastrocnemii, likely from their wrapping around the posterior aspect of the tibia. The quadriceps–hamstring co-contraction provided a protective effect on the ACL and reduced peak anterior shear force by 292 N with a co-contraction index increase of 25% from baseline (31%), whereas a quadriceps–gastrocnemius co-contraction index of 61% increased peak anterior shear force by 797 N compared to baseline (42%). An increase in gastrocnemius contraction, which might be required to protect the ankle from the impact with the ground, produced a large quadriceps–gastrocnemius co-activation, increasing peak anterior shear force. A better understanding of each muscle’s contribution to anterior shear force and, consequently, anterior cruciate ligament tension may inform subject-specific injury prevention programs and rehabilitation protocols.